Five new species of the genus Sinophorus Förster (Hymenoptera, Ichneumonidae, Campopleginae) from China - Han, Yuan-Yuan; van Achterberg, Kees; Chen, Xue-Xin (Zootaxa, 2021)
Five new species of the genus Sinophorus Förster, 1869 (Ichneumonidae, Campopleginae) are described and illustrated from China: S. dioryctriae sp. nov., S. latistrigis sp. nov., S. neimengensis sp. nov., S. petilidentis sp. nov. and S. spissus sp. nov. A key to the Chinese species of Sinophorus is provided.